PERANCANGAN KEMASAN KARUPUAK PADEH PADA USAHA DIO BERSAUDARA DI KOTA PAYAKUMBUH - Mardiah Velanisa, Zubaidah, Syafwan (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
Packaging design purposes Karupuak Padeh Dio Bersaudara are: (1) With the design of the packaging is more familiar karupuak padeh. (2) With the new packaging can increase the interest of the consumer to buy the product. (3) To facilitate the distribution and can be used as a media campaign that is more interesting. The analysis used the SWOT analysis (Strength, Weakness, Opportunity, Threat) analysis because it can solve problems that arise in the design process. This design has been through the design process. This design results in the form of packaging cardboard box measuring 30 cm long, 20 cm wide and 10 cm high and face packs to lay out karupuak padeh, padeh karupuak writing, illustration karupuak padeh, rumah gadang, accompanied marawa as a symbol of Minangkabau colors (black, red, yellow). It is also designed media support in the form of T-shirts, aprons, hats, bags, plates, stickers, miniature freight cars.Kata kunci: Dio Bersaudara, kemasan, karupuak padeh.